Simulations in Decision Making - Rupnik, Bojan (Digital Transformation in Logistics and Supply Chain Management, 2026)
Logistical, production, transportation, and all related issues in the industry follow similar processes, with time being the crucial factor. While some processes can be relatively easily analysed due to their simplicity, the more interconnected the processes are, the more challenging it becomes to describe them accurately using traditional analytical approaches. Simulations, in this regard, provide a deeper insight into the flow of such processes. They enable the analysis of efficiency, shortcomings, and, most importantly, allow for the examination of existing systems under different conditions without interfering with their operation. Besides having a good understanding of the processes, data support is crucial for simulation. This support can involve the recording of historical data and predicting future events with possible alternative scenarios. By enabling real-time data logging during process execution and providing the data to an active simulation that processes it in real-time, a digital twin can be created. Within the scope of this subject, participants familiarize themselves with server systems, queuing systems, discrete event simulations, and the tools that support them, along with examples of their application in manufacturing, logistics, and transportation scenarios.